1996
DOI: 10.1007/bf00311679
|View full text |Cite
|
Sign up to set email alerts
|

Internal stenting of the hepaticojejunostomy and pancreaticojejunostomy in patients undergoing pancreatoduodenectomy to promote earlier discharge from hospital

Abstract: Internal stenting of the hepaticojejunostomy and pancreaticojejunostomy was performed in 11 consecutive patients undergoing pancreatoduodenectomy between July 1992, and July 1994, to promote earlier discharge from hospital. Although minor leakage of the pancreaticojejunostomy occurred in 4 patients, this resolved within a short period and all 11 patients were able to be discharged by the 29th postoperative day in good health and without any intubation. Follow-up abdominal X-ray and computed tomography (CT) sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 10 publications
0
34
0
Order By: Relevance
“…Internal stents have documented reduced rates of POPF in some prospective non randomized studies [66,67] but on the other hand, stents have not been beneficial in some well designed studies [68,69]. A recent meta-analysis by Zhou et al (comparing internal pancreatic stents versus no stents) showed that stents did not reduce the risk of fistula but may even increase the risk of fistula in a soft pancreas [70].…”
Section: Role Of Stentsmentioning
confidence: 99%
“…Internal stents have documented reduced rates of POPF in some prospective non randomized studies [66,67] but on the other hand, stents have not been beneficial in some well designed studies [68,69]. A recent meta-analysis by Zhou et al (comparing internal pancreatic stents versus no stents) showed that stents did not reduce the risk of fistula but may even increase the risk of fistula in a soft pancreas [70].…”
Section: Role Of Stentsmentioning
confidence: 99%
“…The use of a transanastomotic stent for internal or external drainage of pancreatic juice has been advocated by some authors to prevent pancreatic fistula [2,11,12,13,14,15,16,17]. Theoretically, a stent may help divert away the pancreatic secretion from the anastomosis, and it also allows more precise placement of sutures, thus protecting the pancreatic duct from suture injury and reducing the risk of iatrogenic pancreatic duct occlusion.…”
Section: Introductionmentioning
confidence: 99%
“…Yoshimi et al reported their results of inserting an intraductal plastic stent for splinting the pancreatojejunostomy in 11 patients. 18 Although a pancreatic fistula developed in 4 patients, 22 Patients with temporary, external drainage had significantly lower incidences of pancreatic fistula and pancreatojejunostomy insufficiency and a shorter hospital stay. The two (2.7%) patients who died were from the nonstented group.…”
Section: Discussionmentioning
confidence: 98%
“…Ligation of the pancreatic duct 12,13 and occlusion with prolamin 14 or fibrin glue 15 have all been abandoned as methods of anastomotic protection in pancreatic head resection. Instead, concepts such as drainage of the pancreatic duct without a pancreatojejunal anastomosis, 16 internal stenting of the pancreatic duct, [17][18][19] and external drainage of pancreatic juice via a jejunal loop 20 have been implemented. Moreover, both intravenous and subcutaneous preparation of the somatostatin analogue, octreotide, have been widely used to reduce pancreatic secretion after pancreatic head resection.…”
Section: Introductionmentioning
confidence: 99%